Komunikasi Antar Suku dikalangan Mahasiswa Etnik Batak Toba, Etnik Nias, dan Etnik Karo di rumah Baca Silangkitang - Natasya Margaretta Napitupulu; Raikhapoor Raikhapoor (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Indonesia is known as a country rich in cultural diversity, including the diversity of tribes and ethnicities spread throughout the archipelago. Interethnic interaction is a very important phenomenon in reflecting social harmony and cultural diversity in the midst of community life. In the context of students, ethnic diversity is often an interesting element because it involves a cross-cultural communication process, which can enrich understanding and strengthen social relations.Students from the Batak, Nias, and Karo ethnicities, who live or work at the Silangkitang Reading House, have a unique opportunity to interact directly with fellow individuals from different cultural backgrounds. The reading house as a public space not only functions as a place to gain knowledge, but also as an arena for social and cultural interaction. In this interaction, communication is a central element that determines how inter-ethnic relations are established.